Business students' learning and assessment in a COVID-19 world: empirical evidence from Finland - Miihkinen Antti (Routledge Journals, Taylor & Francis Ltd, 2025)
This study examines business students' learning and assessment under remote teachings during the COVID-19 pandemic in a well-established Finnish university. A survey method is used to collect information on 336 business students including 42 accounting students. As indicated by students' responses, a majority of the students succeeded in assessing and self-regulating their learning, but a considerable group of students failed in this task. Students gave a lot of positive feedback on supervised electronic exams, such as scheduling efficiency, improved ability to focus, and reduced stress level. Students also reported a low number of monitoring problems in these exams. Furthermore, the results provide evidence that some students see the risk that problems in monitoring coursework threaten the value of their university degrees. However, about half of the students did not want to increase monitoring. Accounting students' opinions were mostly similar to those of the other business students. This study contributes to the literature by showing key factors that influence students' learning in remote teaching under abnormal conditions. In addition, it demonstrates how the constructivist model of learning can be used to explain students' learning and assessment in these circumstances.